Characterization of rubberwood particleboard made using carboxymethyl starch mixed with polyvinyl alcohol as adhesive - Junidah, Lamaming; Heng, Ng Boon; Owodunni, Amina Adedoja; Sofie Zarina, Lamaming; Nurul Khizrien, Abd Khadir; Rokiah, Hashim; Othman, Sulaiman; Mohamad Haafiz, Mohamad Kassim; Mohd Hazwan, Hussin; Yazmin, Bustami; Mohd Hazim, Mohamad Amini; Salim, Hiziroglu (Elsevier Ltd., 2020)
The aim of the study was to produce and characterize the modified starches and their suitability as wood adhesive for the particleboard manufacturing. The adhesive properties and particleboard manufactured from rubberwood using the modified starch and modified starch mixed with polyvinyl alcohol (PVA) were evaluated. Mixing of PVA with modified starch reduced the viscosity but increased the solid content and thermal property of the modified starch. Particleboard bonded with modified starch mixed with PVA also had improvement in physical and mechanical properties, showing great potential of modified starch and PVA as an adhesive for the green particleboard with good properties.